Exploring the Crossroads of Animal Medicine: Assessing its Potential Impact on Human Health – A Comprehensive Mixed-Methods Investigation through Systematic Literature Review, Pharmacovigilance Approaches, and Netnographic Analysis - JOSIE DUNN (2024)
The misuse of veterinary drugs has emerged as a significant public health concern with growing evidence of their infiltration into both illicit drug markets and recreational use. This study aimed to investigate veterinary drug misuse through various methodologies, including systematic literature review, pharmacovigilance data approaches, and social media analysis. The systematic review of 66 articles identified 28 veterinary drugs being misused by humans, primarily α-2 and β-2 adrenergic receptor agonists, GABAergic modulators, opioid receptor agonists, NSAIDs, and NMDA receptor antagonists. These drugs were misused for purposes such as recreational use, pain relief, weight loss, bodybuilding, and stress-related self-medication, with common routes of administration being parenteral, oral, and inhalation. The motivations for their misuse ranged from affordability and accessibility to the ease of obtaining multiple prescriptions from various veterinary sources. Veterinary workers and individuals with access to animals were particularly prone to misuse. A pharmacovigilance analysis using the FAERS database analysed 21 veterinary drugs, retrieving 38,756 adverse events. A total of 9566 fatalities were recorded for the specific veterinary drugs, with the highest number of reports from the United States (13,532), followed by Canada (2869), and the United Kingdom (1400). For the eight drugs licensed exclusively for animals, most reports were related to levamisole, pentobarbital, and xylazine. Polysubstance use was evident in 90% of the drugs examined, with benzodiazepines (BZDs)/Z-drugs and opioids constituting the most prevalent co-used drug classes. Drugs such as xylazine, pentobarbital, phenylbutazone, and acepromazine were particularly concerning due to their rising use in these contexts, due to being animal drugs identified on a human-centric reporting system. A netnographic, dual-method analysis of social media discussions on Reddit revealed significant trends related to the misuse of xylazine, carfentanil, medetomidine, pentobarbital, phenylbutazone, and acepromazine. Common themes included motivations for misuse, adverse effects, and public perceptions. The combination of manual and AI-driven analysis provided deeper insights into these discussions, understanding the need for proactive monitoring of online platforms as early indicators of emerging drug misuse trends. Collectively, this research emphasises the increasing misuse of veterinary drugs and the need for heightened vigilance in both healthcare and public health policy to address the growing risks of overdose, dependence, and illicit drug adulteration.